Finite-Element Modelling of the Newborn Eardrum - Qi, Li; Funnell, Robert J. (CMBES Proceedings, 2002)
There are a lot of changes in the anatomy of the middle ear between newborn and adult. Our work focuses on the development of finite-element models that describe the biomechanics of the newborn middle ear. The finite-element model has realistic dimensions and geometry based on very high-resolution histological data sets. Ranges of plausible values for the thickness, stiffness and Poisson’s ratio of the eardrum were used and simulated displacement patterns of the eardrum were studied.